Cardiovascular autonomic neuropathy in adolescents and young adults with type 1 and type 2 diabetes: The SEARCH for Diabetes in Youth Cohort Study. Issue 4 (2nd January 2018) - Jaiswal, Mamta; Divers, Jasmin; Urbina, Elaine M; Dabelea, Dana; Bell, Ronny A; Pettitt, David J; Imperatore, Giuseppina; Pihoker, Catherine; Dolan, Lawrence M; Liese, Angela D; Marcovina, Santica; Linder, Barbara; et al.
Abstract : Objective: To estimate the prevalence of and risk factors for cardiovascular autonomic neuropathy (CAN) in adolescents and young adults with type 1 and type 2 diabetes enrolled in the SEARCH for Diabetes in Youth Study. Methods: The study included 1646 subjects with type 1 diabetes (age 18 ± 4 years, diabetes duration 8 ± 2 years, HbA1c 9.1 ± 1.9%, 76% non‐Hispanic Whites) and 252 with type 2 diabetes (age 22 ± 4 years, diabetes duration 8 ± 2 years, HbA1c 9.2 ± 3.0%, 45% non‐Hispanic Blacks). Cross‐sectional and longitudinal risk factors were assessed at baseline and follow‐up visits. Area under the curve (AUC) was used to assess the longitudinal glycemic exposure and cardiovascular risk factors. CAN was assessed by time and frequency domain indices of heart rate variability (HRV). CAN was defined as the presence of ≥3 of 5 abnormal HRV indices. Results: The prevalence of CAN was 12% in adolescents and young adults with type 1 diabetes and 17% in those with type 2 diabetes. Poor long‐term glycemic control (AUC HbA1c), high blood pressure, and elevated triglyceride levels were correlates of CAN in subjects with type 1 diabetes. In those with type 2 diabetes, CAN was associated with elevated triglycerides and increased urinary albumin excretion. Conclusions: The prevalence of CAN in this multiethnic cohort of adolescents and young adults with type 1 and type 2 diabetes are comparable to those reported in adults with diabetes. Suboptimal glycemic control and elevated triglycerides were the modifiable risk factors associated with CAN.